Obligatoryjne zarządzenie wykonania kary warunkowo zawieszonej. Uwagi na tle wyroku Trybunału Konstytucyjnego z 17 lipca 2013 r. oraz uchwały Sądu Najwyższego z 27 marca 2014 r. - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The study concerns mandatory conditions for cancelling the conditional suspension of sentence. The provision referred to concerns Article 75§1 of the Polish Penal Code which has been declared unconstitutional from the perspective of the judgment of the Constitutional Tribunal of 17 July 2013. This ruling shall trigger a whole series of consequences regarding conditional suspension of sentence and other similar regulations in the criminal law.
Keywords: probacja (prawo); nakaz wykonania kary; warunki rządzące porządkiem